Clinical Profile And Liver Functions In Dengue Fever - Sadiq, Saeeda; Mobeen, Amna; Ashraf, Naveed; Hashmi, Fasih; Munir, Shahzad; Ahmad, Anam (Journal of Rawalpindi Medical College, 2024)
Objective: This cross-sectional study explores the complex effects of dengue fever on liver functions in individuals admitted to a Federal Government Polyclinic Hospital (PGMI), in Islamabad Methods: This prospective cross-sectional study evaluated 60 children aged 1–12 years with confirmed dengue, categorized into dengue fever and dengue hemorrhagic fever groups, admitted to a hospital in Islamabad over six months in 2022. Liver function tests and clinical parameters were analyzed using SPSS to compare outcomes, with statistical significance set at p < 0.05. Results: With a mean patient age of 7.23 ± 3.58 years and a male-to-female ratio of 1.22:1, our third-day results showed increased ALT in 50% of cases, AST in 71.7%, and STB in 13.3% of patients. By the seventh day, the corresponding percentages had increased to 68.3%, 96.7%, and 81.7%, respectively. Remarkably, AST exceeded ALT in 50% of cases on day three and in 43% of cases on day seven. Except for STB on day three (p = 0.435), mean ALT, AST, and STB levels were significantly higher in patients with Dengue Hemorrhagic Fever (DHF) on days three and 7 (p < 0.000). Conclusion: This study demonstrated a significant correlation between liver function and dengue fever, with a more substantial effect observed in patients with plasma leakage or DHF. It becomes clear that monitoring liver function in dengue-infected individuals is essential for prompt intervention and improved clinical care. Keywords: Hepatomegaly, Severe Dengue, Vomiting, Liver function tests.